Hermeneutics and Politics: Rereading the Political Unconscious - Robert T. Tally Jr. (Revista Guillermo de Ockham, 2022)
As Karl Marx said in the eleventh of his “Theses on Feuerbach”, “Philosophers have hitherto only interpreted the world in various ways; the point is to change it”. The urgency, as well as the truth of this statement, is undoubtedly as powerful today as when Marx first wrote it. However, as a popular catchphrase frequently cited by radical thinkers and activists, Thesis 11 has unfortunately become a relatively simplistic rejection of the theory in favor of a somewhat anti-intellectual view of praxis. Such is the danger of a wisdom expressed in a way that it can fit on a bumper sticker, a fate that Marx himself probably never imagined for this scathing remark. Marxism, after all, implies the dialectical unity of theory and practice, and Marx himself, of course, spent his life engaged in critical analysis or interpretation of modern capitalist societies, while remaining committed to the movement dedicated to changing the world. The essence of Thesis 11, in fact, lies not so much in the opposition between theory and practice, but in the connection that Marx makes between interpreting the world and changing it. Although interpretation is not an end, it is absolutely essential for any project to be able to imagine alternatives and transform the status quo. In this situation, hermeneutics inevitably acquires a political and critical importance. Arguably, it always carried such weight, but it has become more urgent in our time. Perhaps the very act of interpretation is itself also a political act, which is intimately connected with the project of criticism.